2011
DOI: 10.1042/cs20100476
|View full text |Cite
|
Sign up to set email alerts
|

Aging and vascular endothelial function in humans

Abstract: Advancing age is the major risk factor for the development of CVD (cardiovascular diseases). This is attributable, in part, to the development of vascular endothelial dysfunction, as indicated by reduced peripheral artery EDD (endothelium-dependent dilation) in response to chemical [typically ACh (acetylcholine)] or mechanical (intravascular shear) stimuli. Reduced bioavailability of the endothelium-synthesized dilating molecule NO (nitric oxide) as a result of oxidative stress is the key mechanism mediating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
555
5
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 575 publications
(587 citation statements)
references
References 190 publications
(265 reference statements)
18
555
5
9
Order By: Relevance
“…Endothelial dysfunction is the major antecedent to atherosclerosis, a predictor of clinical CVD risk, and is linked to many common disorders of aging including cognitive impairments, Alzheimer's disease, motor dysfunction, insulin resistance, and sarcopenia (Heitzer et al ., 2001; Gokce et al ., 2002; Lakatta & Levy, 2003; Widlansky et al ., 2003; Seals et al ., 2011, 2014). We have previously demonstrated that arterial SIRT1 activity is reduced with aging and contributes to the age‐related impairment in endothelial function (Donato et al ., 2011; Gano et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelial dysfunction is the major antecedent to atherosclerosis, a predictor of clinical CVD risk, and is linked to many common disorders of aging including cognitive impairments, Alzheimer's disease, motor dysfunction, insulin resistance, and sarcopenia (Heitzer et al ., 2001; Gokce et al ., 2002; Lakatta & Levy, 2003; Widlansky et al ., 2003; Seals et al ., 2011, 2014). We have previously demonstrated that arterial SIRT1 activity is reduced with aging and contributes to the age‐related impairment in endothelial function (Donato et al ., 2011; Gano et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…NMN supplementation completely restored EDD by restoring NO‐mediated dilation. The improvement in EDD with NMN treatment in old mice was not due to an increase in vascular smooth muscle sensitivity to NO because NMN did not influence dilation in response to administration of a NO donor (sodium nitroprusside), that is, a dilation that is not induced by endothelial NO production (Seals et al ., 2011). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulated redox signaling and increased ROS production with aging lead to endothelial dysfunction, thereby contributing to the pathogenesis of cardiovascular diseases, such as coronary artery diseases, hypertension, and atherosclerosis, in elderly patients (Ungvari et al ., 2010). An increase in ROS generation reduces NO bioavailability through several mechanisms including a direct interaction between NO and ROS, resulting in vascular dysfunction (Donato et al ., 2007; Ungvari et al ., 2008; Seals et al ., 2011). However, little is known about the mechanism by which ECs preserve their function of relaxing vascular smooth muscle during aging‐related oxidative stress.…”
Section: Introductionmentioning
confidence: 99%